Dynamic seeding versus microinjection of mesenchymal stem cells for acellular nerve allograft: an in vitro comparison. Issue 8 (August 2022) - Bedar, Meiwand; Jerez, Sofia; Pulos, Nicholas; van Wijnen, Andre J.; Shin, Alexander Y.
Summary: Background: Mesenchymal stem cell (MSC)-supplemented acellular nerve allografts (ANA) are a potential strategy to improve the treatment of segmental nerve defects. Prior to clinical translation, optimal cell delivery methods must be defined. While two techniques, dynamic seeding and microinjection, have been described, the seeding efficiency, cell viability, and distribution of MSCs in ANAs are yet to be compared. Methods: Sciatic nerve segments of Sprague-Dawley rats were decellularized, and MSCs were harvested from the adipose tissue of Lewis rats. Cell viability was evaluated after injection of MSCs through a 27-gauge needle at different flow rates (10, 5, and 1 µL/min). MSCs were dynamically seeded or longitudinally injected into ANAs. Cell viability, seeding efficiency, and distribution were evaluated using LIVE/DEAD and MTS assays, scanning electron microscopy, and Hoechst staining. Results: No statistically significant difference in cell viability after injection at different flow rates was seen. After cell delivery, 84.1 ± 3.7% and 87.8 ± 2.8% of MSCs remained viable in the dynamic seeding and microinjection group, respectively ( p  = 0.41). The seeding efficiency of microinjection (100.4%±5.6) was significantly higher than dynamic seeding (48.1%±8.6) on day 1 ( p  = 0.001). Dynamic seeding demonstrated a significantly more uniform cell distribution over the course of the ANA compared to microinjection (p  = 0.02) . Conclusion: MSCs remain viable after both dynamic seeding and microinjection in ANAs. Higher seeding efficiency was observed with microinjection, but dynamic seeding resulted in a more uniform distribution. In vivo studies are required to assess the effect on gene expression profiles and functional motor outcomes.